2008
DOI: 10.1038/ijir.2008.42
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, low testosterone levels and erectile dysfunction

Abstract: Obesity is an important risk factor for many common diseases including cardiovascular disease (CVD), type 2 diabetes, cancer and erectile dysfunction (ED). Adipose tissues produce a number of adipokines and cytokines, which affect endothelial and metabolic function resulting in insulin resistance and the metabolic syndrome (risks factors for CVD). Both ED and metabolic syndrome improve with a reduction in body mass index (BMI). The relationships among obesity, metabolic syndrome, ED, sex hormonebinding globuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 96 publications
7
73
2
4
Order By: Relevance
“…17,34,35 In contrast, other studies correlated lower HDL-c and higher triglyceride levels were significantly with LST in T2DMs. 9,36 In the present study, smoker ratio was significantly higher in MHG patient but regression analysis showed no significant correlation between smoking and MHG, The relation of smoking with testosterone was controversial, some studies had shown a positive association between smoking and total or FT levels, also smoking cessation decreased testosterone levels in men followed for idiopathic infertility, while some studies found no association.…”
Section: Discussionmentioning
confidence: 52%
“…17,34,35 In contrast, other studies correlated lower HDL-c and higher triglyceride levels were significantly with LST in T2DMs. 9,36 In the present study, smoker ratio was significantly higher in MHG patient but regression analysis showed no significant correlation between smoking and MHG, The relation of smoking with testosterone was controversial, some studies had shown a positive association between smoking and total or FT levels, also smoking cessation decreased testosterone levels in men followed for idiopathic infertility, while some studies found no association.…”
Section: Discussionmentioning
confidence: 52%
“…14 In another study, health professionals found that patients with a BMI >28.7 kg/m 2 had a 30% higher risk of ED compared to those with a BMI <23.2 kg/m 2 . 15 However, there is still disagreement in the literature on whether obesity behaves as an isolated risk factor for ED. A study coordinated by Feldman et al 16 did not demonstrate any correlation between obesity and ED in the general population, but these authors stated that obesity correlates with other comorbidities such as hypertension, dyslipidemia, thyroid disease and diabetes mellitus, which have direct correlations with ED.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, testosterone deficiency has been reported in population studies to be associated with an increase in all-cause mortality, and this has been shown to be accounted for mainly by CVD (Khaw et al 2007, Vikan et al 2009, Araujo et al 2011. Moreover, accumulating evidence suggests that testosterone deficiency is an independent cardiovascular risk factor and many recent reviews have focussed on the link between hypogonadism, MetS, T2DM and CVD (Makhsida et al 2005, Shabsigh et al 2008, Corona et al 2009, Diaz-Arjonilla et al 2009, Jones & Saad 2009, Stanworth & Jones 2009, Traish et al 2009, Zitzmann 2009a, Grossmann et al 2010, Jones 2010a,b, Muraleedharan & Jones 2010, Moulana et al 2011, Wang et al 2011, Saad et al 2012, Salam et al 2012.…”
Section: Introductionmentioning
confidence: 99%